2012
DOI: 10.3109/10428194.2012.695359
|View full text |Cite
|
Sign up to set email alerts
|

Potential application ofIDH1andIDH2mutations as prognostic indicators in non-promyelocytic acute myeloid leukemia: a meta-analysis

Abstract: Recurrent mutations of isocitrate dehydrogenase isoforms 1 and 2 (IDH1 and IDH2) have recently been studied in adult patients with acute myeloid leukemia (AML). A meta-analysis was performed to demonstrate their controversial prognostic impacts. The associations of IDH1 or IDH2 mutations with other molecular abnormalities were also investigated. In patients with AML, IDH1/2 mutations were significantly associated with normal karyotype and isolated trisomy 8 (p < .05). After adjusting for well-studied prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 24 publications
3
38
1
1
Order By: Relevance
“…Besides, IDH mutations are particularly common in cytogenetically normal AML patients (CN-AML; ref. 9). For these reasons, prognostic availability of IDH mutations in IR-AML patients should be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, IDH mutations are particularly common in cytogenetically normal AML patients (CN-AML; ref. 9). For these reasons, prognostic availability of IDH mutations in IR-AML patients should be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, gene mutations of isocitrate dehydrogenase 1 and 2 (IDH1 and IDH2) were reported recently not only in gliomas but also in AML (4,5). The prognostic significance of these mutations appears controversial in AML (6)(7)(8)(9)(10), although a metaanalysis suggests a poor outcome in cases with IDH1 mutations (11).…”
mentioning
confidence: 99%
“…The recommendation for testing of other mutations in AML is supported by 21 studies, † † † † † comprising one SR based meta-analysis, 353 13 were deemed to have a low to moderate risk of bias, § § § § § and one was deemed to have a moderate risk of bias. 29 None of those studies were found to have methodological flaws that would raise concerns about the studies' findings.…”
mentioning
confidence: 99%
“…Among studies of the effect of isocitrate dehydrogenase 1 (IDH1) mutation R132 in adult AML, one meta-analysis 353 found the mutation associated with a worse EFS, but not associated with OS. One NRCT 354 found the mutation to be associated with a worse OS and DFS, but that study combined the results of IDH1 and IDH2 mutations.…”
mentioning
confidence: 99%
See 1 more Smart Citation